LARANGAN BUANG HAJAT MENGHADAP ATAU MEMBELAKANGI KIBLAT: TELAAH HADIS MUKHTALIF - Amrullah; Ahmad Diaz Syahrezyah Makmur; Irfan Jaya Sakti (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Ar-Rahman, 2025)
Hadith is one of the main sources of Islamic law that has high authority after the Qur'an. However, in their application, there are traditions that appear to be contradictory, thus requiring a special approach in understanding and resolving the differences. This study examines the mukhtalif traditions related to the prohibition and permissibility of facing or facing away from the Qibla when relieving oneself, using the descriptive analytical method to examine the text and context aspects of the traditions. The results show that the differences in the traditions can be resolved by the method of al-jam'u wa al-taufiq (harmonizing the arguments). The prohibition of facing or turning away from the Qibla applies to open places, such as the desert, as a form of respect for the Qibla. Conversely, the permissibility applies in closed places, such as latrines or toilets, which are considered not intended for prayer. This finding confirms that there is no substantial contradiction in these traditions if they are understood contextually and in accordance with the principles of Shari'a.